Situated Learning and Teacher Identity: Insights From Malaysian TESL Pre-Service Teachers’ Practicum Experience - Wong, Yee Von; Lim, Seong Pek (Pedagogika, 2025)
This study discussed Malaysian TESL pre-service teachers’ (PSTs) identity development during practicum. Using Situated Learning Theory (SLT) as a theoretical lens, the semi-structured interviews with 18 PSTs identified family support, culturally sensitive mentoring and reflective practices as important social and cultural factors in TESL-PSTs’ identity formation. The study discussed practical implications for improving teacher education programmes in line with Sustainable Development Goal 4 (SDG 4).